2020
DOI: 10.15252/embr.201948938
|View full text |Cite
|
Sign up to set email alerts
|

MEX3A regulates Lgr5 + stem cell maintenance in the developing intestinal epithelium

Abstract: Intestinal stem cells (ISCs) fuel the lifelong self‐renewal of the intestinal tract and are paramount for epithelial repair. In this context, the Wnt pathway component LGR5 is the most consensual ISC marker to date. Still, the effort to better understand ISC identity and regulation remains a challenge. We have generated a Mex3a knockout mouse model and show that this RNA‐binding protein is crucial for the maintenance of the Lgr5+ ISC pool, as its absence disrupts epithelial turnover during postnatal developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 78 publications
(98 reference statements)
6
29
0
Order By: Relevance
“…Mex3A appears crucial for the maintenance of the slowly cycling subpopulation of lgr5+ gut stem cells (Chatterji and Rustgi, 2018), and lgr5 absence in Mex3A −/− mice leads to growth retardation, postnatal mortality, and severe impairment of intestinal crypt development (Pereira et al, 2020). Recent data showed that MEX3A is up-regulated in glioblastoma specimens (Bufalieri et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mex3A appears crucial for the maintenance of the slowly cycling subpopulation of lgr5+ gut stem cells (Chatterji and Rustgi, 2018), and lgr5 absence in Mex3A −/− mice leads to growth retardation, postnatal mortality, and severe impairment of intestinal crypt development (Pereira et al, 2020). Recent data showed that MEX3A is up-regulated in glioblastoma specimens (Bufalieri et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, human MEX3A is necessary to post-transcriptionally regulate the levels of CDX2 , mRNA coding for an intestinal transcription factor required in gastrointestinal homeostasis ( Pereira et al, 2013 ). Mex3A appears crucial for the maintenance of the slowly cycling subpopulation of lgr5+ gut stem cells ( Chatterji and Rustgi, 2018 ), and lgr5 absence in Mex3A –/– mice leads to growth retardation, postnatal mortality, and severe impairment of intestinal crypt development ( Pereira et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with the idea that Mex3a high cells are LRCs, they are enriched in BMI1, Lrig1, Tert and Hopx and display a low proliferation. A recent study also confirmed the role of Mex3a in the maintenance of the Lgr5 + ISC pool and further showed that it does so possibly by suppressing PPARγ signaling (Pereira et al 2020 ). PPARγ-selective agonists reduce the number and size more markedly in Mex3a KO organoids than WT organoids, which are consistent with the observation that Mex3a downregulates PPARγ expression and high PPARγ signaling impairs Lgr5 + ISCs (Pereira et al 2020 ).…”
Section: Quiescent Stem Cellsmentioning
confidence: 66%
“…In addition, ISCs may originate from a possible dedifferentiation of TACs or Paneth cells into Lgr5+ cells in response to Wnt3A or irradiation [ 15 ]. Interestingly, it was also revealed that a pool of Lgr5+ cells expressing the RNA-binding protein Mex3a are crucial for maintaining the Lgr5+ ISC pool in case of injury [ 16 ].…”
Section: Isc Niche Structure and Functional Organizationmentioning
confidence: 99%